Thinking in Categories of Multivariant Future - Eckard Minx; Ewald Bohlke (Foresight and STI Governance, 2008)
Complex and implicit issues of utilizing scenario method in strategic planning are considered. Special emphasis is placed on a gap between future visions and related actions of politicians and business actors that prevents efficient decision-making on the national level. Authors not only reveal existing contradictions but also attempt to explain their causes and recommend solutions to overcome the problem. They propose an unconventional approach - scenario design of the future. It allows revealing relations between various complex phenomenons, comparing consequences of alternative development pathways and make better decisions. Keywords: strategic planning; strategic thinking; strategic management